2008
DOI: 10.1007/s00442-008-1131-x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf size and leaf display of thirty-eight tropical tree species

Abstract: Trees forage for light through optimal leaf display. EVective leaf display is determined by metamer traits (i.e., the internode, petiole, and corresponding leaf), and thus these traits strongly co-determine carbon gain and as a result competitive advantage in a light-limited environment. We examined 11 metamer traits of sun and shade trees of 38 coexisting moist forest tree species and determined the relative strengths of intra-and interspeciWc variation. Species-speciWc metamer traits were related to two vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
2
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 66 publications
7
111
2
7
Order By: Relevance
“…To account for light-related variation, we recorded the crown exposure (1-5, ranging from no direct light to full direct light) of each sampled tree as a proxy for canopy openness (Poorter and Rozendaal 2008). From each tree, two branches located at similar crown positions were selected, placed in sealed plastic bags, and stored in a cooler.…”
Section: Functional Traitsmentioning
confidence: 99%
“…To account for light-related variation, we recorded the crown exposure (1-5, ranging from no direct light to full direct light) of each sampled tree as a proxy for canopy openness (Poorter and Rozendaal 2008). From each tree, two branches located at similar crown positions were selected, placed in sealed plastic bags, and stored in a cooler.…”
Section: Functional Traitsmentioning
confidence: 99%
“…Leaf size and other functional traits are key determinants of plant performance in ecosystems (Blonder et al, 2011;Sack et al, 2012;Wright et al, 2004) and vary across complex environmental gradients such as elevation, topography and variations in factors related to climate (Buot and Okitsu, 1999;Klich, 2000;Körner, 2007;Poorter and Rozendaal, 2008;Thomas, 2011). Identifying how leaf traits change along these various gradients is an indispensable first step toward understanding the functional adaptations of plants to the environment (Castro-Díez et al, 2000;Dörken and Stützel, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested that leaf thickness increases with altitude, while frequency of leaf and size of leaf decreases [21,22,23]. Fibrous and thin leaves are more capable of rolling because of intensive sclerification [24] and it protecting their stomata from directs exposure to external environments [25].…”
Section: Resultsmentioning
confidence: 99%